Influência da sazonalidade no valor nutricional de ostras (Crassostrea rhizophorae) cultivadas na Barra de São Miguel-AL - Pascoal, Jadna Cilene Moreira (2008)
Shellfish is considered to be a food of great nutritional importance. However, various intrinsic and extrinsic factors influence the chemical composition of a species of shellfish. Seasonal variability is one of the variables that influence the proximate composition and, especially, the lipid profile of the shellfish principally when it concerns the fatty acids and cholesterol. In this work, important aspects were reviewed involving differences in the levels of total lipids, fatty acids and cholesterol as a function of the seasonal fluctuations of various species of shellfish. Considering the scarcity of data in scientific literature on regional food, the influence of seasonal variation on the nutritional value was evaluated of the mangrove oysters (Crassostrea rhizophorae) cultivated at Barra de São Miguel, Alagoas, Brazil. In its natural form, during summer and winter, the proximate composition, calorific value, fatty acid profile, cholesterol and cholesterol oxides as well as the nutritional quality index of the lipids were determined. The results obtained from the oysters collected during summer and winter respectively were: moisture (82.52% and 82.83%), proteins (11.05% and 12.89%), carbohydrates (2.05% e 0.57%), ash (1.69% and 1.50%), lipids (2.69% and 2.50%), calories (76.61 Kcal/100g and 76.34 Kcal/100g), fatty acids (polyunsaturated 34.21% and 41.93%, omega-3 29.05% and 37.16%), cholesterol (48.99 mg/100g and 54.43 mg/100g) and cholesterol oxides (7-ketocholesterol 2.3 μg/g and 9.2 μg/g), allowing us to conclude that seasonal variation influences the nutritional value of the oysters, as those collected during winter had advantages in terms of nutrition due to elevated levels of protein and of EPA and DHA omega-3 fatty acids and lower total lipid and saturated fatty acid levels. These results could contribute to a greater dissemination of the consumption of the oysters.